PENGELOLAAN KELAS ( Korelasi Pengaturan Ruang Kelas Dengan Prestasi Belajar Bidang Studi Pendidikan Agama Islam di SMPN 2 Mantup - Lamongan) - Yudha Eko Susanto; Muhtadi; Abdul Rouf (Arsy : Jurnal Studi Islam, 2020)
The objective of this study is to determine the correlation between classroom setting with student achievement. Based on the results of this study, it was found that the classroom setting was not significantly related with student learning outcomes of Islamic Religion Course, because it is based on the results of the study population consisted of 529 students with a total of 96 students was listed as sample (approximately 20% from the total population), it was known that N or the amount of research data is 96. The significance value is 0.418 (p> 5%), thus, Ho is accepted and it means there is no corellation between the classroom setting with student achievement of Islamic Religious Course.However, seating arrangement and classroom setting is necessary in the learning process because it can affect the students’ learning environment. Therefore, it is expected that each student should be able to experience to sit in the front, middle and back seat in the learning process, because the seating arrangement can make their learning becomes fun.